James Moran, Modernists and the Theatre: The Drama of W. B. Yeats, Ezra Pound, D. H. Lawrence, James Joyce, T. S. Eliot and Virginia Woolf (Methuen Drama, 2022) - Lupi, Andrea (Margins/Marges/Margini, 2025)